Soft-tissue profile changes of patients with Class II and Class III malocclusion treated with conventional orthognathic surgery and surgery first approach - Janson, Gabriela (2025)
Introduction: Facial aesthetics hold great importance in modern society. The SurgeryFirst Approach (SF) has become an alternative to the Conventional Orthognathic Surgery of Three Phases (COS), delivering facial enhancements early in treatment by eliminating the pre-orthodontic phase. Nonetheless, a comparison of the final softtissue profile changes between these methods remains unexplored. Objectives: To compare the soft tissue profile changes of both orthodontic-surgical approaches. Methods: For Class II, COS group comprised 23 patients (10 male, 13 female) with a mean age of 27.56 (± 8.52) years, treated with Conventional Orthognathic Surgery of Three Phases. SF group comprised 23 patients (16 male, 7 female) with a mean age of 30.23 (± 8.31) years, treated with Surgery-First Approach. And for Class III, COS group comprised 23 patients (13 male, 10 female) with a mean age of 28.84 years (± 8.12) years and SF group comprised 23 patients (9 male, 14 female) with a mean age of 25.33 years (± 6.88) years, treated with the surgery first approach. Soft tissue profile changes were evaluated at pre- and posttreatment in lateral radiographs. Intergroup comparisons were performed using T-test (P<0.05). Results: For Class II malocclusion, the COS group showed reduced maxillary length, greater mandibular growth, and larger decreases in FMA and SN.GoGn, while the SF group exhibited increased soft tissue convexity and mentolabial angle. Upper lip and anterior maxilla thickness increased more in COS. At post-treatment, significant differences were found in NAP, mentolabial angle, and lower lip thickness. For Class III malocclusion, the COS group showed a reduced nasolabial angle during treatment, whereas the SF group showed an increase. At post-treatment, cephalometric variables were similar between groups. Conclusion: Both groups presented similar soft tissue changes at the end of treatment. SF group presented the advantage to provide better esthetics immediately after surgery.